Insight into the mechanism of end-of-day far-red light (EODFR)-induced shade avoidance responses in Arabidopsis thaliana. Issue 12 (2nd December 2015) - Mizuno, Takeshi; Oka, Haruka; Yoshimura, Fumi; Ishida, Kai; Yamashino, Takafumi
Abstract: Shade avoidance responses are changes in plant architecture to reduce the part of a body that is in the shade in natural habitats. The most common warning signal that induces shade avoidance responses is reduction of red/far-red light ratio perceived by phytochromes. A pair of basic helix–loop–helix transcription factors, named PHYTOCHROME-INTERACTING FACTOR 4 (PIF4) and PIF5, is crucially involved in the shade avoidance-induced hypocotyl elongation in Arabidopsis thaliana . It has been recently reported that PIF7 also plays a role in this event. Here, we examined the involvement of these PIFs in end-of-day far-red light (EODFR) responses under light and dark cycle conditions. It was shown that PIF7 played a predominant role in the EODFR-dependent hypocotyl elongation. We propose the mechanism by which PIF7 together with PIF4 and PIF5 coordinately transcribes a set of downstream genes to promote elongation of hypocotyls in response to the EODFR treatment. Graphical abstract: : PIF7-dependent EODFR responses are observed immediately after the FR light treatment, while PIF4/PIF5 dependent responses are observed at the end of night. PIF7 and PIF4/5 regulate downstream target genes independently in an additive manner.